Intellectual Disability and Autism Spectrum Disorders: Causal Genes and Molecular Mechanisms - Srivastava, Anand K. (2014)
Intellectual disability (ID) and Autism Spectrum disorder (ASD) are the most common developmental disorders present in humans. Combined, they affect between 3-5% of the population. Additionally, they can be found together in the same individual thereby complicating treatment. The causative factors (genes, epigenetic and environmental) are quite varied and likely interact so as to further complicate the assessment of an individual patient. Nonetheless, much valuable information has been gained by identifying candidate genes for ID or ASD. Understanding the etiology of either ID or ASD is of utmost importance for families. It allows a determination of the risk of recurrence, the possibility of other comorbidity medical problems, the molecular and cellular nature of the pathobiology and hopefully potential therapeutic approaches.